1986
DOI: 10.1021/ja00271a074
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic displacement as a function of hydration number and temperature: rate constants and product distributions for OD-(D2O)0,1,2,3 + CH3Cl at 200-500 K

Abstract: Nucleophilic displacement reactions which are exothermic do not react on every collision in the gas phase.6,7 They exhibit a negative temperature dependence, rate constants decreasing with increasing temperature,8 and reaction at 300 K is quenched dramatically by the addition of only one-three solvate molecules.9In each respect nucleophilic displacement differs from proton transfer, as contrasted in the companion paper.10 Here we report how hydration influences the rate constant and the product distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
70
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 1 publication
6
70
1
Order By: Relevance
“…We have previously reported similar behavior for the reactions of OH -(H 2 O) 0-2 with CH 3 Cl. 23 As in the present study, the CH 3 Cl rate constants decrease with increasing reactant solvation, the decrease being even larger than that found here. We attribute this latter observation to the fact that the reaction of OH -with CH 3 Cl is less exothermic (and hence more sensitive to reactant stabilization) than is the reaction with CH 3 Br.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…We have previously reported similar behavior for the reactions of OH -(H 2 O) 0-2 with CH 3 Cl. 23 As in the present study, the CH 3 Cl rate constants decrease with increasing reactant solvation, the decrease being even larger than that found here. We attribute this latter observation to the fact that the reaction of OH -with CH 3 Cl is less exothermic (and hence more sensitive to reactant stabilization) than is the reaction with CH 3 Br.…”
Section: Discussionsupporting
confidence: 48%
“…16,17,37 The amount of hydration in the products can also be compared to our previous study of OH -(H 2 O) 0-2 with CH 3 Cl. 23 In that study, we found that 15% of the product was hydrated in the n )1 reaction and 40% for the n ) 2 reaction. Both of these values are similar to the corresponding results in the present study.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…(3)) using a variety of experimental techniques [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. By performing these kinds of experiments it is hoped to gain additional insight into the intrinsic contribution of the solvent molecules to the progress [25] of these reactions.…”
Section: Introductionmentioning
confidence: 99%
“…For most mono-solvated reactions only a small fraction of the leaving groups are solvated (Eq. (4)) [11][12][13][14][15][16][19][20][21][22]24,25], even though this reaction pathway is more exothermic than formation of the non-solvated leaving group (Eq. (5)).…”
Section: Introductionmentioning
confidence: 99%